A Moral-Protective Dating Relationship Model: Integrating Islamic Law and Indonesian Positive Law: Model Relasi Moral-Protektif dalam Pacaran: Integrasi Hukum Islam dan Hukum Positif Indonesia - Abdul Wasik; Ryan Fachryan Lesmana Putra; Moh Khusnul Khuluq (jsd: Journal of Society and Development, 2026)
This article develops a moral-protective relationship model for examining dating as a social category with moral and legal consequences rather than as an independent legal category. This normative legal study employs statutory, conceptual, and normative-comparative approaches. Its sources include the Qur’an, Qur’anic exegesis, legislation, legal scholarship, academic articles, and reports issued by state institutions. The analysis proceeds through the inventory of norms, interpretation of Islamic texts and positive-law provisions, synchronization of norms, identification of convergences and differences, and conceptual model construction. The findings show that Islamic law provides preventive moral boundaries through the protection of dignity, self-restraint, the prohibition against approaching zina, and the prohibition of injustice. Indonesian positive law does not criminalize dating as a relationship status, but it provides protection when the relationship involves assault, unlawful deprivation of liberty, threats, sexual violence, exploitation, violence against children, or electronically facilitated violence. Integrating these frameworks produces a moral-protective relationship model consisting of four dimensions: propriety, responsibility, protection, and victim recovery. The model positions moral prevention and legal protection as complementary layers. The study implies that relationship education should integrate religious values, legal literacy, and accessible victim-protection mechanisms. Its originality lies in formulating a conceptual-normative model that links Islamic moral boundaries with positive-law protection in addressing violence within dating relationships.